Financial security of banks: recognition system threats and eliminating risks - Гребенюк, Наталя Олександрівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
Issues of financial security of banks in the context of potential threats detection and prevention of their implementation into risks are considered in the paper. The concept of financial security of banks together with the need to maintain continuous financial flows is clarified. A logical and functional scheme of the system for preventive recognition of potential threats and eliminating risks for the financial security of banks is also developed. Its structure includes functional, methodological, and object-targeted level.It is not possible to estimate the quality and efficiency of the system with the direct financial figures, because the main purpose of its activities is to prevent realization of potential threats.The concept of threats to the bank's financial security received the further development due to explaining and accounting the effect of irrational expectations. The classification of threats to the bank’s security is completed. It includes exogenous and endogenous factors  together with current trends of increasing influence of anthropogenic factors and aggravation of conflicts at various levels, such as military, corporate, stakeholders, bank-staff, and bank-customer. The analysis of the statistics of the banking system functioning under conditions of the current crisis is made. A cricial diagnosis of the banks operations was conducted by the National Bank of Ukraine. The major risks to the bank’s operations and failures up to date are revealed.The objects of management of the system’s information security are described in details depending on the source of emergence and storage of data. The arrangements for potential threats prevention to the implementation of the Internet-banking by introducing advanced methods of validation of information are proposed.It is proved that an effective system of preventive detection of potential threats and elimination of risks in the bank's financial security should include: complete automation of solutions with minimal manual intervention, embedded advanced analytical models of elimination of distorted information, flexible and effective cooperation with customers, and resistance to changes in the regulatory framework and unlawful actions of competitors and criminals.